On Teaching Hardware/Software Co-design using FPGA - Bencheva, N.; Kostadinov, N.; Ruseva, Y. (Elektronika ir Elektrotechnika, 2010)
At Ruse University in the Faculty of Electrical Engineering, Electronics and Automation the students are offered several introductory courses that focus on microcontroller-based systems, embedded programming and Programmable Logic Design. In the process of design, configuration, and programming of microprocessors it is hard for the students to optimize the division of functions between hardware and software. One of the reasons is the growing number of advanced programming techniques and design principles, as well as sophisticated Integrated Development Environments. The courses have a fixed number of hours and the teacher cannot extend the content of the lectures and the labs. In order to improve the students’ knowledge and skills in the process of embedded systems design, the Hardware/Software Co-design is used in the teaching process. The paper considers one example of implementation of this approach in the design of a traffic light controller. The project is based on the Intellectual Property Core of PicoBlaze microcontroller, embedded within Xilinx Field Programmable Gate Array Families. For the project development Evaluation Board Spartan 3E including XC3S500E FPGA device is used.